The Philosophy of Nyaya and Nyaya Methodology: A Lens for Mathematics Learning - G.C., Laxmi; Pokhrel, Maheshwor (Education and Development, 2025)
This study explores the relevance of Nyaya philosophy, a classical Indian system of logic, epistemology, and debate, as it applies to mathematical learning and research methodology. Rooted in the principles of Hindu philosophy, the Nyaya system offers a structured approach to knowledge acquisition, logical reasoning, and inferential proof that can significantly enhance critical thinking and problem-solving skills in mathematics education. This paper employs a systematic literature review methodology and adheres to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines to ensure transparency and rigor. A comprehensive search was conducted across academic databases, ancient texts, and contemporary scholarly works related to Nyaya epistemology and its intersections with mathematical reasoning. The inclusion criteria focused on sources that explicitly discussed logical structures, inference methods, and pedagogical applications relevant to Nyaya philosophy and mathematics. Data were synthesized thematically to identify key philosophical constructs and their applicability to modern mathematical instruction. The analysis reveals that the Nyaya theory of knowledge (pramana), and its emphasis on perception (pratyaksha), inference (anumana), comparison (upamana), and testimony (shabda), provide a robust framework for understanding and validating mathematical proofs. The systematic nature of Nyaya's logical discourse mirrors the deductive reasoning used in mathematical theorems and problem-solving strategies. Furthermore, the study highlights how integrating Nyaya’s inferential methods into mathematics education can foster deeper conceptual understanding, logical clarity, and analytical reasoning among learners. It also underscores the importance of preserving and adapting indigenous knowledge systems for contemporary pedagogical practices.